2020
DOI: 10.1111/cns.13387
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamic functional connectivity in Alzheimer’s disease

Abstract: Aims Alzheimer's disease (AD) is a progressive neurodegenerative disorder. Previous studies have demonstrated abnormalities in functional connectivity (FC) of AD under the assumption that FC is stationary during scanning. However, studies on the FC dynamics of AD, which may provide more insightful perspectives in understanding the neural mechanisms of AD, remain largely unknown. Methods Combining the sliding‐window approach and the k‐means algorithm, we identified three reoccurring dynamic FC states from resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 56 publications
23
66
0
Order By: Relevance
“…The global state in the present study characterized by a whole brain connectivity profile with absence of strong negative correlations that participants spend most of their time in this state. This finding is in accordance with previous findings in healthy participants (Allen et al, 2014; Cabral et al, 2017; Larabi et al, 2020), AD and dementia (Fu et al, 2019; Gu et al, 2020; Jones et al, 2012; Niu et al, 2019; Schumacher et al, 2019), aging (Tian et al, 2018; Viviano et al, 2017), and other psychiatric and neuro-degenerative diseases (Figueroa et al, 2019; Kim et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The global state in the present study characterized by a whole brain connectivity profile with absence of strong negative correlations that participants spend most of their time in this state. This finding is in accordance with previous findings in healthy participants (Allen et al, 2014; Cabral et al, 2017; Larabi et al, 2020), AD and dementia (Fu et al, 2019; Gu et al, 2020; Jones et al, 2012; Niu et al, 2019; Schumacher et al, 2019), aging (Tian et al, 2018; Viviano et al, 2017), and other psychiatric and neuro-degenerative diseases (Figueroa et al, 2019; Kim et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The other recurring FC state that AD patients had lower probability of occurrence and spent less time compared to HC subjects are located in SMN-sub-VIS networks. Decreased ability access to brain areas were located mainly in DMN, SN, FPN, SMN, sub and VIS networks in AD patients compared to HC subjects consistent with many previous findings (Brier et al, 2012; Dai et al, 2015; Greicius et al, 2004; Gu et al, 2020; Mosimann et al, 2004; Schumacher et al, 2019). For the DMN,FPN and SN, the decreased access to these networks might be associated with impaired cognitive functions, as the DMN plays a pivotal role in essential cognitive processes (Buckner et al, 2008; Zhao et al, 2018) and especially influences memory consolidation (Greicius et al, 2004), and the FPN is involved in cognitive control and has also been reported to be also affected by AD (Zhao et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations